(Val8)GLP‐1‐Glu‐PAL: a GLP‐1 Agonist That Improves Hippocampal Neurogenesis, Glucose Homeostasis, and β‐Cell Function in High‐Fat‐Fed Mice. Issue 4 (8th November 2012) - Lennox, Rachael; Porter, David W.; Flatt, Peter R.; Gault, Victor A.
Abstract This study examined the biological properties of a novel GLP‐1 peptide, (Val8)GLP‐1‐Glu‐PAL, engineered with an Ala8→Val8 substitution and additional incorporation of a C16 fatty acid moiety at Lys26 via a glutamic acid linker. GLP‐1 underwent 75 % degradation by DPP‐IV over 8 h, whereas (Val8)GLP‐1 and (Val8)GLP‐1‐Glu‐PAL remained intact. All GLP‐1 peptides significantly stimulated insulin secretion at 5.6 mM (1.3‐ to 4.9‐fold, p<0.01 to p<0.001) and 16.7 mM glucose (1.5‐ to 2.3‐fold, p<0.001). At higher concentrations (Val8)GLP‐1‐Glu‐PAL was significantly more potent at stimulating insulin secretion (1.2‐ to 1.3‐fold, p<0.05). In high‐fat‐fed mice, all GLP‐1 peptides significantly lowered plasma glucose concentrations (41–66 % decrease, p<0.05 to p<0.001), with (Val8)GLP‐1‐Glu‐PAL eliciting protracted glucose‐lowering actions (32–59 % decrease, p<0.05 to p<0.01) when administered 8 h prior to a glucose load. Twice‐daily administration of (Val8)GLP‐1‐Glu‐PAL in high‐fat‐fed mice for 21 days had no effect on bodyweight or food intake, but significantly lowered non‐fasting plasma glucose (43–46 % decrease, p<0.05). (Val8)GLP‐1‐Glu‐PAL markedly decreased glycemic excursion following intraperitoneal glucose (32–48 % decrease, p<0.05), enhanced insulin response to glucose (2‐ to 2.3‐fold, p<0.05 to p<0.01), and improved insulin sensitivity (25–38 % decrease in plasma glucose, p<0.05). O2 consumption, CO2 production, RER, and energy expenditure were not altered by (Val8)GLP‐1‐Glu‐PAL therapy. Treatment with (Val8)GLP‐1‐Glu‐PAL resulted in a significant increase in BrdU‐positive cells (1.3‐fold, p<0.05) in the granule cell layer of the dentate gyrus. These data demonstrate that (Val8)GLP‐1‐Glu‐PAL is a long‐acting GLP‐1 peptide that significantly improves hippocampal neurogenesis, glucose homeostasis, and insulin secretion in high‐fat‐fed mice.